Challenges faced by students in conducting research project at Kenya Medical Training College - Macharia, Elizabeth W.; Kahiri, Mary W. (International Journal Of Community Medicine And Public Health, 2024)
Background: Kenya Medical Training College (KMTC) is a public middle-level college that trains and develops multidisciplinary health professionals mainly at the diploma level. To ensure graduates provide evidence-based services, diploma students conduct research projects during their training. The researchers aimed to determine the main challenges students face while conducting research projects. The specific objectives were to explore student and lecturer behaviour towards research projects, find out student perceptions, establish institutional infrastructure supporting research work, and assess the quality of students’ research projects. Methods: The study population included KMTC students enrolled in basic diploma courses, targeting third-year students conducting research projects and their supervisors. A cross-sectional research design was used, with structured and semi-structured questionnaires administered to students and lecturers. Seven campuses were sampled randomly, with a sample size of 384 respondents used. Data was analyzed using SPSS and presented in graphs, figures, tables, and percentages. Results: The main challenges identified were difficulties in holding timely meetings with supervisors (42.6% strongly agreeing, 29.9% agreeing). There was a shortage of supervisors, delaying the marking of research work (41.3% strongly agreed, 30.2% agreed). Availability of laptops, accessibility to journals, and internet connectivity were major challenges. Over 50% of respondents had difficulties in the research process. Conclusions: The most agreed problem by most KMTC students was lack of time to conduct research, financial constraints and lack of enabling environment.